2014
DOI: 10.1371/journal.pone.0089839
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood Chronic Physical Aggression with a DNA Methylation Signature in Adult Human T Cells

Abstract: BackgroundChronic physical aggression (CPA) is characterized by frequent use of physical aggression from early childhood to adolescence. Observed in approximately 5% of males, CPA is associated with early childhood adverse environments and long-term negative consequences. Alterations in DNA methylation, a covalent modification of DNA that regulates genome function, have been associated with early childhood adversity.AimsTo test the hypothesis that a trajectory of chronic physical aggression during childhood is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 103 publications
2
55
0
6
Order By: Relevance
“…Indeed, in another study performed by our group, we observed similar DNA methylation signatures associated with childhood CPA in women (n=430 promoters) as seen in men, where 31 gene promoters were significantly associated in both sexes (Guillemin et al, 2014). Interestingly, a significant portion of this overlap is due to identical genomic sites being differentially methylated in a gender-independent fashion.…”
Section: Reviewsupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, in another study performed by our group, we observed similar DNA methylation signatures associated with childhood CPA in women (n=430 promoters) as seen in men, where 31 gene promoters were significantly associated in both sexes (Guillemin et al, 2014). Interestingly, a significant portion of this overlap is due to identical genomic sites being differentially methylated in a gender-independent fashion.…”
Section: Reviewsupporting
confidence: 75%
“…Moreover, these cytokines were also shown to be repressed in men with CPA compared with men on a normative developmental trajectory of aggressive behaviour (Provençal et al, 2013b). Interestingly, one of these downregulated cytokines in men with CPA, interleukin-6 (IL-6), was previously shown to be involved in aggressive behaviour in mice, because its knockout (IL-6 −/− ) resulted in an increased aggressive behaviour phenotype in these mice (Alleva et al, 1998).…”
Section: Epigenetic Associations With Aggressive Behaviourmentioning
confidence: 99%
“…1b) (Day & Sweatt, 2010;Kovatsi et al, 2011;Provencal et al, 2014;Roth & Sweatt, 2010). The epigenetic factor, especially DNA methylation is the most important aspect of behavioral disorders with marked alteration in the DNA methylation pattern in the brain which leads to memory formation (Day & Sweatt, 2010).…”
Section: Anti-social and Aggressive Behavior Identificationmentioning
confidence: 99%
“…Ces soins modifient, dans l'hippocampe, l'épigénome d'un gène clé, celui qui code le récepteur aux glucocorticoïdes, mais également l'épigénome de réseaux de gènes [4]. Des mécanismes semblables opèrent chez le rongeur, le macaque et l'humain [5,6], montrant la conservation entre les espèces des mécanismes impliqués dans de tels processus d'adaptation à l'environnement. Des mécanismes épigéné-tiques ont depuis été impliqués dans les effets, sur la progéniture, de divers stimulus environnementaux subis à différents stades par la mère ou par le père : nutrition déséquilibrée, adversité, stress, peur du prédateur, défaite sociale, etc.…”
unclassified
“…Des mécanismes épigéné-tiques ont depuis été impliqués dans les effets, sur la progéniture, de divers stimulus environnementaux subis à différents stades par la mère ou par le père : nutrition déséquilibrée, adversité, stress, peur du prédateur, défaite sociale, etc. [5,[7][8][9][10][11][12]] (➜). …”
unclassified